A corny conundrum: a rare case of cornual ectopic pregnancy - Ravali, Nichanametla; R., Sheela S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Ectopic pregnancy is one of the obstetrical emergencies, identifying ectopic and early intervention and management places a crucial role in saving one’s life. This life-threatening emergency is one of the important causes for maternal morbidity and mortality. In this case study we report a 22-year-old primigravida who presented to R. L. Jalappa hospitals emergency department with severe pain abdomen, with history of 3 months of amenorrhea, unsure of her last menstrual period, on examination her vitals were unstable and diffuse tenderness noted on per abdomen examination, ultrasound showing ruptured ectopic pregnancy, patient was managed successfully through emergency exploratory laparotomy with unilateral salphingectomy.